Ob-Gyn Clinic Online Scheduling System - Justine May T. Reguyal; Ann Michelle S. Agno; Mariel C. Martinez; Jocelyn T. Castro; Bennydick VC. Cariazo; Cris Norman P. Olipas; Rachel T. Alegado (Formosa Journal of Computer and Information Science, 2023)
This study aimed to design, develop, and assess an Ob-gyn Clinic Online Scheduling System using the stages of the software development life cycle. The respondents were IT experts and end-users who were purposively sampled from the Science City of Munoz, Nueva Ecija, Philippines. The system was evaluated using the International Organization for Standardization (ISO) 25010 software standards. The results indicated that the SDLC model was effective in designing and developing such a system. The IT experts and end-users assessed the technical features and quality of using the system and gave favorable and acceptable ratings. The developed system was intended to help hospitals in accommodating their outpatients, particularly pregnant women or people with uterus problems, by making it easier for them to schedule their available time, date, or days and reducing their time spent waiting for their turn. Based on the assessment, the researchers recommended that this study could serve as a first step for gynecologists in developing the easiest way to schedule. Future researchers were encouraged to investigate the benefits and drawbacks of the system and its effects on patients and gynecologists. Understanding this research could assist future researchers in developing better systems